Noteworthy records for Tantilla cascadae and T. ceboruca (Squamata: Colubridae) from Jalisco, Mexico - Cruz Sáenz, Daniel; Muñoz Nolasco, Francisco Javier; Lazcano, David; Flores Covarrubias, Edgar (2015)
We report the first records of two species of snake in the state of Jalisco, Mexico. We recorded one specimen of Tantilla cascadae and two of Tantilla ceboruca, the former known only from its type locality. These findings extend the known geographical distribution of T. cascadae 121 km westward from Michoacán, its type locality. Also, it extends the known geographical distribution of T. ceboruca 41 km eastward from its type locality and 185 km northwest from its second record in the state of Colima.